Brain‐gut psychotherapies: Promising tools to address gastrointestinal problems in patients with eating disorders. Issue 6 (19th May 2021) - Wildes, Jennifer E.; Bedell, Alyse; Graham, Andrea K.; Kells, Meredith
Abstract: Gastrointestinal (GI) problems are common in individuals with eating disorders (EDs) and associated with distress, impairment, and increased healthcare utilization. GI symptoms may be exacerbated by meals and other interventions central to ED recovery thereby contributing to negative clinical outcomes. Informed by models emphasizing the role of the brain‐gut axis in the expression of GI symptoms, this article describes a program of research to adapt "brain‐gut psychotherapies" for EDs. First, the role of the brain‐gut axis in GI symptoms is described, and evidence‐based brain‐gut psychotherapies are reviewed, with an emphasis on cognitive behavioral therapy for GI disorders and gut‐directed hypnotherapy. Next, future directions for research in EDs to (a) understand the impact of GI symptoms on illness course and outcome; (b) clarify target engagement; (c) evaluate brain‐gut psychotherapies; and (d) optimize intervention reach and delivery are described. We present a conceptual model that emphasizes GI‐specific anxiety and altered gut physiology as targets of brain‐gut psychotherapies in EDs, and discuss several issues that need to be addressed in designing clinical trials to test these interventions. We also describe how engagement with multidisciplinary stakeholders and use of digital tools could speed translation from the laboratory to clinical settings.